2018
DOI: 10.1007/s13197-018-3441-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rosemary extract and lactic acid on the quality of refrigerated broiler fillets

Abstract: The current study investigated the effect of rosemary extract (0.2% RE) and lactic acid (1% LA) on some freshness, bacterial parameters and formation of biogenic amines during refrigeration of broiler fillets. Ninety broiler fillet samples were divided into three groups (each 30). The control group was dipped in sterile distilled water, while the RE and LA groups were dipped in rosemary extract 0.2% (w/v) and lactic acid 1% (w/v), respectively. Sensory evaluation, pH, total volatile basic nitrogen (TVB-N), thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…According to a study, packaging infused with 2% rosemary EO decreased Pseudomonas (by roughly 2 log CFU/g) and LAB counts in fresh chicken breasts stored at 4 • C for 8 and 16 days, respectively (Petrová et al, 2013). A related study found that dipping broiler fillets in 0.2% rosemary extract and 1% lactic acid lowered the psychrotrophic bacteria and Enterobacteriaceae of broiler fillets and increased the acceptability of refrigerated broiler fillets during storage by decreasing the biogenic amine index and rancidity (Hussein et al, 2018). More research is required to obtain comprehensive knowledge about the impact of these natural antimicrobial agents on the safety of chicken products, as well as their effects on product sensory attributes.…”
Section: Natural Antimicrobialsmentioning
confidence: 99%
“…According to a study, packaging infused with 2% rosemary EO decreased Pseudomonas (by roughly 2 log CFU/g) and LAB counts in fresh chicken breasts stored at 4 • C for 8 and 16 days, respectively (Petrová et al, 2013). A related study found that dipping broiler fillets in 0.2% rosemary extract and 1% lactic acid lowered the psychrotrophic bacteria and Enterobacteriaceae of broiler fillets and increased the acceptability of refrigerated broiler fillets during storage by decreasing the biogenic amine index and rancidity (Hussein et al, 2018). More research is required to obtain comprehensive knowledge about the impact of these natural antimicrobial agents on the safety of chicken products, as well as their effects on product sensory attributes.…”
Section: Natural Antimicrobialsmentioning
confidence: 99%
“…counts by 1.3 and 1.1 log 10 CFU/ml, respectively, and psychrophilic bacteria by 1.8 and 1.3 log 10 CFU/ml, respectively, on chicken samples. e application of lactic acid at 1% demonstrated interesting preservative effects on the quality of refrigerated chicken broiler fillets in terms of freshness (significant decrease of TVBN and TBARS values), great control of microbial parameters (reduction of total psychrotrophic bacteria and Enterobacteriaceae loads), and inhibition of biogenic amine formation which increase the acceptability of refrigerated chicken meat up to 12 and 15 days at 4°C [84].…”
Section: Poultry Meat Productsmentioning
confidence: 99%
“…Growing the poultry business, which is a quick and more affordable source of proteins, can help Egypt tackle its serious challenge of rising demand for animal proteins. Egypt lacks red meat, hence chicken meat is regarded as a substantial source of protein in Egypt due to the lack of red meat production (Hussein et al, 2018). Numerous earlier studies emphasized the primary points of contact between contaminated chicken meat and consumers, from the point of slaughter to the ready-to-eat meat meal (Rouger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%